High pressure processing to control Salmonella in raw pet food without compromising the freshness appearance: The impact of acidulation and frozen storage. (February 2023) - Serra-Castelló, Cristina; Possas, Arícia; Jofré, Anna; Garriga, Margarita; Bover-Cid, Sara
Abstract: The trend of feeding dogs and cats with raw pet food claiming health benefits poses health concerns due to the occurrence of pathogenic bacteria. High pressure processing (HPP) allows the non-thermal inactivation of microorganisms, preserving the nutritional characteristics with minimal impact on organoleptic traits of food. The present study aimed to evaluate and model the effect of HPP application (450–750 MPa for 0–7 min) on the inactivation of Salmonella, endogenous microbiota and colour of raw pet food formulated with different concentrations of lactic acid (0–7.2 g/kg) as natural antimicrobial. Additionally, the effect of a subsequent frozen storage of pressurized product was assessed. Salmonella inactivation ranged between 1 and 9 log, depending on the combination of conditions. According to the polynomial model obtained, the effect of pressure was linear, while a quadratic term was also included for holding time (depicting the occurrence of a resistant tail at ca . 4–6 min). The effect of lactic acid was dependent on the pressure level, being most relevant for treatments below 600 MPa. Frozen storage after HPP prevented the pathogen recovery and caused a further Salmonella inactivation enhanced by lactic acid in most of the treatments. Endogenous microbial groups were significantly reduced by HPP to below the detection level in several conditions. In general, little effect of HPP on the instrumental colour parameters was observed, except for a slight increase in lightness, which was hardly appreciable from visual observation. High pressure processing emerges as a relevant technology for the control of Salmonella spp. and to manage the microbiological safety of raw pet food. The mathematical model can be used as decision support tool to design safer raw pet food, while keeping the desired freshness appearance of the products. Highlights: Pressure, time and lactic acid determines HPP inactivation of Salmonella in raw pet food. HPP inactivation is enhanced in acidulated raw pet food. HPP causes minimal changes in the appearance of raw pet food.